2013
DOI: 10.1016/j.bmc.2012.10.056
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationships of antitubercular salicylanilides consistent with disruption of the proton gradient via proton shuttling

Abstract: A series of salicylanilides was synthesized based on a high-throughput screening hit against Mycobacterium tuberculosis. A free phenolic hydroxyl on the salicylic acid moeity is required for activity, and the structure-activity relationship of the aniline ring is largely driven by the presence of electron withdrawing groups. We synthesized 94 analogs exploring substitutions of both rings and the linker region in this series and we have identified multiple compounds with low micromolar potency. Unfortunately, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…Subunit A of VirB8sp structure (PDB http://www.rcsb.org/pdb/search/structidSearch.do?structureId=2BHM ) and VirB8sp M102R (PDB http://www.rcsb.org/pdb/search/structidSearch.do?structureId=5JBS) were used for docking analyses. Docking simulations were conducted using AutodockTools software . Polar hydrogen atoms were added to the protein structures and Gaisteger charges were calculated for each atom.…”
Section: Methodsmentioning
confidence: 99%
“…Subunit A of VirB8sp structure (PDB http://www.rcsb.org/pdb/search/structidSearch.do?structureId=2BHM ) and VirB8sp M102R (PDB http://www.rcsb.org/pdb/search/structidSearch.do?structureId=5JBS) were used for docking analyses. Docking simulations were conducted using AutodockTools software . Polar hydrogen atoms were added to the protein structures and Gaisteger charges were calculated for each atom.…”
Section: Methodsmentioning
confidence: 99%
“…A screen of a subset of the US National Institutes of Health Chemical Genomics Centre's compound library against M. tuberculosis identified salicylamide analogue 361 (IMD‐0354) as a hit antimycobacterial compound, albeit with significant cytotoxicity against murine macrophages . Compound 361 has previously been identified as a candidate for the treatment of chronic asthma, through the inhibition of IκB kinase (IKK) β as well as displaying encouraging utility as an inhibitor of the type II transmembrane serine protease TMPRSS4, which is involved in colon cancer metastasis and invasion, in addition to good activity against breast cancer stem cells and C. albicans .…”
Section: Tuberculosismentioning
confidence: 99%
“…Mixed results from the evaluation of numerous analogues of 361 featuring altered ring substituents, substitution patterns, as well as amide bioisosteres for activity against M. tuberculosis suggested that there was limited scope for optimisation. However, compound 362 and MMV687807 ( 363 ) both showed a small increase in antimycobacterial activity, still with significant cytotoxicity . The acetate analogue of 361 ( 364 ) showed improved activity against M. tuberculosis coupled to a significant decrease in cytotoxicity, which led the authors to speculate that the MOA of these compounds involves disruption of the mitochondrial proton gradient, and that 364 is selectively activated by M. tuberculosis …”
Section: Tuberculosismentioning
confidence: 99%
“…It is interesting that the active salicylanilides 29, 37, 38, and 40 closely resemble niclosamide, an old nitro-substituted salicylanilide teniacide thought to function by uncoupling oxidative phosphorylation. Due to the low antischistosomal selectivity of these salicylanilides, consistent with previous investigations (15) of this compound class, salicylanilides will be challeng- The following scaling factors were applied to mouse liver microsome calculations: liver mass ϭ 54.9 g liver/kg body weight; microsomal protein mass ϭ 47 mg/g liver mass; and hepatic blood flow (Q) ϭ 120 ml/min/kg body weight (32). UD, unable to be determined.…”
Section: Discussionmentioning
confidence: 87%